Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm doing some work in linear algebra and these came up and I realized I don't know how to solve them as they have quadratics in them. I'm sure I've done this before but if someone could give me a crash course on how to find the values of the variables, it would be most appreciated. For the following questions, let $a,b,c,d \in \mathbb{R}$


$\begin{cases} a^2+b^2=a\\ (a+d)b=b\\ b^2+d^2=d \end{cases}$


$\begin{cases} a^2+bc=a\\ (a+d)b=b\\ (a+d)c=c\\ bc+d^2=d \end{cases}$

share|cite|improve this question
$a,b,c,d$ are reals? Or integers? – Inceptio May 29 '13 at 4:50
@Inceptio They are all real numbers. – Sujaan Kunalan May 29 '13 at 4:52
up vote 0 down vote accepted


$\begin{cases} a^2+b^2=a\\ (a+d)b=b\\ b^2+d^2=d \end{cases}$

in equation $2$ divide both side by b $\begin{cases} a^2+b^2=a\\ a+d=1\\ b^2+d^2=d \end{cases}$

from eqn $2$ and $3$

$$a=1-d$$ $$b^2=d-d^2$$

put these value in eqn $1$

$$(1-d)^2+d-d^2=1-d\implies d=0$$ it will give $a=1,b=0$

2) $\begin{cases} a^2+bc=a\\ (a+d)b=b\\ (a+d)c=c\\ bc+d^2=d \end{cases}$

in eqn $2,3$ divide both side by b and c

$ a^2+bc=a\\ a+d=1\\ a+d=1\\ bc+d^2=d $

$ a^2+bc=a\\ a+d=1\\ bc+d^2=d $

from eqn $1$ and $2$ $$bc=a-a^2$$ $$d=1-a$$

put these value in $3$ $$a-a^2+(1-a)^2=1-a\implies a=0$$ that will give $d=1$ and either of b and c will 0. $$$$

share|cite|improve this answer
Many solutions are missing. – André Nicolas May 29 '13 at 5:51
yes it is a one set of solution.If I will substitute different values from different eqn then it will give another set.Should I mention in answer? – iostream007 May 29 '13 at 6:48

I tried to solve 1) in your question. $$\begin{cases} a^2+b^2=a ----(1)\\ (a+d)b=b ----(2)\\ b^2+d^2=d ----(3) \end{cases}$$ when $b=0$, the equations (1) and (3) boil down to $a^2=a$ and $d^2=d$. In this case, we have the solutions below $$\{a=0,b=0,d=0\},\\ \{a=0,b=0,d=1\},\\ \{a=1,b=0,d=0\},\\ \{a=1,b=0,d=1 \}.$$
If $b\ne0$, then equations (1), (2) and (3) becomes \begin{cases} a^2-a +b^2=0 ----(4)\\ a+d =1 -------(5)\\ d^2-d +b^2= 0----(6) \end{cases} From (4),(5)and (6), we can see $a$ and $d$ are the solutions of the equation $x^2-x+b^2=0$, where $b$ can be any real number. So in this case, the solutions could be $$\left\{a=\frac{1}{2} \left(1-\sqrt{1-4 b^2}\right),d=\frac{1}{2} \left(\sqrt{1-4 b^2}+1\right)\right\},\\ \left\{a=\frac{1}{2} \left(\sqrt{1-4 b^2}+1\right),d=\frac{1}{2} \left(1-\sqrt{1-4 b^2}\right)\right\}. $$ Hint: your question 2) can be solved in a similar way.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.